Geodetic Even Decomposition of Graphs: A Mathematical Approach - Merly, E. Ebin Raja; Joel, T. Iwin (Mathematics and Computer Science: Contemporary Developments Vol. 2, 2024)
Graph theory is a mathematical study of the structure of abstract relationships between objects. It is very popular area of discrete mathematics with not only numerous theoretical developments, but also countless applications to practical problems. As a research area, graph theory is still relatively young, but it is maturing rapidly with many deep results having been discovered in the last fifty years. It is fundamental to a number of applied fields including operation research, computer science and social network analysis. Graph theory plays a vital role in mathematics and it has many interesting applications. There are several reasons for the acceleration of interest in graph theory. It has become fashionable to mention that there are applications of graph theory to some areas. The fact is that graph theory serves as a mathematical model for any system involving a binary relation.